First assessment of the prevalence of Trichinella in backyard-raised pigs in Central-Southern Chile - Javiera Guzmán-Faúndez; Vanesa Crisóstomo-Jorquera; Carlos Landaeta-Aqueveque; AnaLía Henríquez (Veterinary Quarterly)
Trichinellosis is a significant zoonotic disease worldwide, with pigs as a primary reservoir host of human infection. Backyard pigs are particularly at risk due to their exposure to muscle tissue containing Trichinella larvae from synanthropic micromammals or home slaughter waste. In Chile, veterinary inspections of domestically slaughtered pigs are mainly conducted in veterinary clinics using muscle samples provided by farmers or consumers. While positive cases must be reported to the authorities, negative cases are not, creating a gap in official data on Trichinella prevalence. This study aimed to assess the prevalence of Trichinella sp. in backyard and intensively raised pigs in south-central Chile. Records of 2,608 backyard pigs were obtained from various veterinary clinics in the La Araucanía and Ñuble regions, with a few records from the El Maule and Biobío regions, encompassing a total of 33 communes. The overall prevalence was found to be 0.9% (95% confidence interval: 0.59–1.37). According to the available information, records of more than 50,000 pigs slaughtered in abattoirs per year corresponded to negative results after examination. Previous reports suggest that eradication is challenging; however, the decreasing incidence rate of human infection indicates the possibility of improving control measures for this zoonosis.